Integration of Digital Technologies in Early Childhood Education: A Critical Review of Benefits, Risks, and Pedagogical Implications - Rita Zubaidah; Hilda Fitriani; Miari Edlin Kuswardani; Khairunnisak Khairunnisak; Fefy Gusmarlia (Institut Nalanda, 2026)
This critical narrative review examines the integration of digital technologies in early childhood education (ECE), synthesizing contemporary evidence on pedagogical benefits, developmental risks, and implementation challenges. Drawing on literature published between 2020 and 2026 retrieved from Google Scholar, the analysis reveals that technology-enhanced learning can support cognitive development, language acquisition, and fine motor skills when implemented through intentional, play-based pedagogies with active adult mediation. Conversely, excessive or unstructured screen exposure is consistently associated with speech delays, socio-emotional difficulties, reduced physical activity, and emerging privacy vulnerabilities. Significant barriers—including teacher preparedness gaps, infrastructural inequities, and the absence of validated assessment frameworks—further complicate equitable and effective integration. The findings underscore that digital tools must function as complements to, rather than substitutes for, embodied and socially interactive learning experiences grounded in developmentally appropriate practice. Recommendations include prioritizing context-sensitive pedagogical guidelines, sustained professional development focused on technological pedagogical content knowledge (TPACK), and policy interventions that address the urban-rural digital divide. This review contributes a nuanced, evidence-informed perspective to guide educators, curriculum designers, and policymakers in navigating the complex intersection of technological innovation and early childhood development.